Formulasi Dan Evaluasi Pasta Gigi Ekstrak Etanol Daun Senggani (Melastoma Malabathricum L) Untuk Perawatan Mulut - Noni Anggela, Rafita Yuniarti (Journal of Health and Medical Science, 2024)
Dental caries is a tooth decay that starts from the surface and develops inwards on the tooth, beginning with the process of demineralization of the tooth. One of the bacteria that causes dental caries is Streptococcus mutans. Senggani leave (Melastoma malabathricum L.) one of the plants that efficacious as a toothache remedy and can inhibit the growth of bacteria on the teeth because it contains secondary metabolite compounds. The objective of the research was to formulate ethanol extract of senggani leave as toothpaste and to find concentration out the of Na-CMC and sorbitol in toothpaste preparations. This research stage included simplicia processing, ethanol extract manufacturing, characteristic examination, phytochemical screening, and making formulations of toothpaste preparations and evaluation tests such as, organoleptis, homogeneity, pH, scattering power and freeze-thaw cycling stability tests. The concentration of ethanol extract of senggani leaves used was 6.25% and concentrations of Na-CMC 3%, 4%, 5%, 6%, 7% and sorbitol 50%, 40%, 20%, 10%, 5%. The fifth result of toothpaste preparations of ethanol extract of senggani leave for organoleptic tests was green moss, spicy taste, flavorful typical of ethanol extract of senggani leave and mint. With a qualified pH value ranging from 6.0-6.7 and a scatter power test ranging from 4.6-6.2 cm. Results of freeze-thaw cycling stability tests showed no changes in organoleptis, and pH of toothpaste. The toothpaste preparation of senggani leave ethanol extract (Melastoma malabathricum L.) could be formulated as a toothpaste and the best formula was formula I with a concentration of Na-CMC 3% and sorbitol of 50%.